1997
DOI: 10.1097/00006123-199704000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation for Intractable Pain: A 15-Year Experience

Abstract: DBS in selected patients provides long-term effective pain control with few side effects or complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
198
0
7

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(207 citation statements)
references
References 36 publications
2
198
0
7
Order By: Relevance
“…This is in good agreement with calculations, based on Eq. [1], indicating that the induced voltage should not exceed 4 mV on the small-bore MR scanner for the chosen experimental setup. The induced voltage for the clinical MR scanner with its weaker gradients is even lower (U Ͻ 0.5 mV).…”
Section: Voltagementioning
confidence: 99%
See 1 more Smart Citation
“…This is in good agreement with calculations, based on Eq. [1], indicating that the induced voltage should not exceed 4 mV on the small-bore MR scanner for the chosen experimental setup. The induced voltage for the clinical MR scanner with its weaker gradients is even lower (U Ͻ 0.5 mV).…”
Section: Voltagementioning
confidence: 99%
“…However, about 30% of the patients in whom electrodes were implanted did not improve clinically (1,2).…”
mentioning
confidence: 99%
“…To address this predicament, alongside improving case selection, further challenges are to identify predictors of long-term efficacy and to investigate the putative phenomenon of tolerance. Progressive increases of stimulus amplitude or insertion of a second electrode have proven unhelpful [184]. Our experience [79], and that of others [195], is that tolerance is often overcome by subtle alterations of pulse width by 30-90 μs or frequency by 5-15 Hz, or both, and by either cycling stimulation or having stimulation breaks-periods off DBS lasting from days to months as required.…”
Section: Discussionmentioning
confidence: 99%
“…16 Others reported that deep brain stimulation was non-effective in 3 patients with central pain after SCI. 19 A more rational treatment of central neuropathic pain following SCI should be derived from an increased understanding of the pathophysiology underlying this pain syndrome.…”
Section: Neuropathic Painmentioning
confidence: 99%